Revisión sistemática de la prevalencia de osificación del ligamento estilohioideo. - Rapalino Alvarado, Angie Lorena (Universidad Antonio Nariño, 2021)
Introduction. Eagle syndrome is a rare pathology associated with the presence of symptoms such as otalgia, headache, vertigo, foreign body sensation in the throat, dysphagia, restriction in lateral lateral movements of the neck. It is a problem that occurs only in 4% of the general population, and of this percentage, only 4% suffer from symptoms related to Eagle syndrome, that is, 0.16% of the general population. Objective. Identify the clinical symptoms of Eagle syndrome, its prevalence and imaging characteristics.Methodology. A systematic review of publications in Pubmed, Scopus and Bireme was carried out during the period from 2000 to 2019. Original articles with a cross-sectional, longitudinal design and case studies were chosen. It was complemented with a descriptive study of a series of 35 cases of eagle syndrome from the UAN clinics in Bucaramanga. Results. 25 articles of case reviews, prevalence, frequency and statistical analyzes were analyzed, of which it was found that it is associated in a higher percentage to the female gender, occurring more frequently between an age range of 31 to 50 years and with respect to the multiplicity of symptoms to which it is associated, firstly we found headache with 24%, secondly otalgia with 19%, and thirdly the foreign body sensation with 10%, among others. Conclusions: Headache is the symptom for which patients with eagle syndrome make dental consultation. Imaging classification is necessary and thus timely management of these cases Key words: eagle syndrome, headache, otalgia, myofascial pain.